On the Occurrence of the Blunthead Puffer, Sphoeroides pachygaster (Osteichthyes: Tetraodontidae), in the Strait of Messina (Central Mediterranean). (9th August 2012) - Giordano, D.; Profeta, A.; Pirrera, L.; Soraci, F.; Perdichizzi, F.; Greco, S.; Perdichizzi, A.; Rinelli, P.
Abstract : The record of Sphoeroides pachygaster reveals the presence of the species in the Strait of Messina (Central Mediterranean Sea). The adult species was captured on 15 march 2012. It measured 280 mm of total length and weighed 461.5 g. Morphometric measurements (mm) and meristic counts were reported in this paper.